Medium-term and long-term renal function changes with direct oral anticoagulants in elderly patients with atrial fibrillation - Armentaro, Giuseppe; D’Arrigo, Graziella; Bo, Mario; Cassano, Velia; Miceli, Sofia; Pitino, Annalisa; Tripepi, Giovanni; Romeo, Santina Maria Grazia; Sesti, Giorgio; Lip, Gregory Y. H.; Pastori, Daniele; Gori, Mercedes; et al. (Frontiers in Pharmacology, 2023)
Objective: Atrial Fibrillation (AF) and chronic kidney disease frequently coexist in elderly. Warfarin-like drugs (WLDs) may be associated with a relatively greater decrease of estimated glomerular filtration rate (eGFR) as compared to direct oral anticoagulants (DOACs) but there is no evidence on the medium and long term. To further elucidate this issue in elderly patients with AF, we investigated the renal function deterioration in the two groups of the study (DOACs or WLDs). Patients and Methods: 420 AF patients were enrolled (mean age: 77.0±6.0 years; 136 on WLDs and 284 on DOACs). These patients underwent 3 eGFR measurements during the follow-up period. The between arms difference of eGFR decline over time was investigated by Linear Mixed Models and group-based trajectory model analyses. Results: In the whole study cohort, after a median follow-up of 4.9 years (interquartile range: 2.7-7.0 years), eGFR decreased from 67.4±18.2 to 47.1±14.3 ml/min/1.73 m2 (p<0.001). Remarkably, patients on DOACs experienced a significantly smaller eGFR decline than WLDs patients (-21.3% vs -45.1%, p<0.001) and this was true both in the medium-term (-6.6 vs -19.9 ml/min/1.73m2) and in the long-term (-13.5 versus -34.2 ml/min/1.73m2) period. After stratification into 5 subgroups according to trajectories of renal function decline over time, logistic regression showed that DOACs patients had from 3.03 to 4.24 fold greater likelihood to belong to the trajectory with less marked eGFR decline over time than WLDs patients. Conclusion: Elderly patients with AF on treatment with DOACs had a relatively smaller decline of eGFR over time as compared to those on treatment with WLDs. This is consistent with what was partly reported in the literature.